The effects of conscious movement investment on inhibiting a simple response - You, Yihong; Weng, Wan-Chun; Suprianto, Gita Benefita; van der Kamp, John (Frontiers in Psychology, 2024)
The relationship between a performer’s conscious involvement or investment in movement control and monitoring and the ability to inhibit the movement is still unclear. We conducted three experiments to investigate whether a higher inclination for conscious movement investment benefits the inhibition of a simple keypress response. In all experiments, the inclination for conscious movement investment was measured with the Movement-Specific Reinvestment Scale. In Experiment 1, participants performed the go/no-go task and conscious investment was manipulated by directing conscious attention either to the finger movement (i.e., internal focus) or to the resulting motion of the key (i.e., external focus). The results showed that neither the participants’ inclination for conscious movement investment, nor the direction of conscious attention affected inhibition performance. In Experiment 2, participants performed the stop-signal task, which is more attention demanding than the go/no-go task. The results showed that participants with a high or low inclination for conscious movement investment did not differ in inhibition performance. In Experiment 3 an ego-depletion procedure was included that limits resources for conscious movement investment. Before and after this ego-depletion procedure, participants performed the stop-signal task. The results showed that participants with a high inclination for conscious movement investment slowed down inhibition when they felt mentally depleted, while no slowing down of inhibition was found among participants who felt less depleted and/or had a low inclination for conscious movement investment. Together, the study provides evidence that increased conscious movement investment is beneficial for movement inhibition. Yet, these effects only emerge against the dynamic background of interacting individual (e.g., inclination for conscious movement investment, available attentional resources) and task constraints (e.g., task difficulty).